Avaliação de danos oxidativos no DNA de linfócitos e estresse oxidativo no plasma de pacientes a cirurgia sob anestesia balanceada com sevoflurano - Orosz, Jose Eduardo Bagnara [UNESP] (2014)
Despite of the anesthetics effectiveness and safety in clinical use, there are some questions to be answered concerning their genotoxicity and effects on cellular redox balance. Only a few studies have evaluated DNA damage or oxidative stress in patients during surgical procedure with the volatile anesthetic sevoflurane. To further understand the possible toxic effects of this agent, the current study aimed to evaluate oxidative DNA damage, lipid peroxidation and plasma antioxidant defense during and after general balanced anesthesia maintained with sevoflurane in 15 adult patients without comorbidities who underwent elective minor surgery. The venous blood samples were collected at baseline-before anesthesia; after anesthesia induction and immediately before surgery; 2 h after the beginning of anesthesia; and on the day following surgery. DNA damage was detected in peripheral lymphocytes using the comet assay, and the enzymes formamidopyrimidine-DNA glycosylase (fpg) and endonuclease III (endo III) were used to recognize oxidized purine and pyrimidine lesions, respectively. Plasma malondialdehyde (MDA) and antioxidant defense were detected by fluorescence. The results showed no increase in DNA damage or base oxidation among the time points evaluated. Balanced anesthesia with sevoflurane did not alter MDA levels, and plasma antioxidant defense was unchanged during or after anesthesia. In conclusion, this study showed, for the first time, that sevoflurane does not lead to oxidation in genetic material or lipids, and does not alter the antioxidant status during or after balanced anesthesia in patients without comorbidities undergoing minimally invasive surgeries